Media internetowe jako element prowadzenia polityki informacyjnej Kościoła katolickiego – studium przypadku diecezji rzeszowskiej - Kuca, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper analyses the use of online media to conduct information policy in the parishes of the Roman Catholic Church in the Rzeszów diocese. The basis for the analysis is provided by two co-authored studies on the information policy of priests in the Diocese of Rzeszów conducted jointly with Dr Zbigniew Chmielewski at the turn of 2012 and 2013, and later repeated in 2018. The research was altogether carried out on the basis of similar methodological assumptions, which were implemented in a series of anonymous questionnaires. The paper focuses on the part of the research that concerned the use of Internet-related (online) media in the communication activities of the parish website, as well as social media (both official parish profiles in social media, as well as private profiles of priests).
Online media as part of the Catholic Church's information policy – a case study of the Rzeszów Diocese
Keywords: Rzeszów Diocese; Catholic Church; online media; social media